Male hormonal contraception: hope and promise. Issue 3 (March 2017) - Piotrowska, Katarzyna; Wang, Christina; Swerdloff, Ronald S; Liu, Peter Y
Summary: Family planning is a shared responsibility, but available male-directed contraceptive methods are either not easily reversible (vasectomy) or not sufficiently effective (condom). However, roughly 20% of couples using a contraceptive method worldwide, and up to 80% in some countries, still choose a male-directed method. Male hormonal contraception is highly effective, with perfect use failure rates of 0·6% (95% CI 0·3–1·1) if sperm concentrations of less than 1 million per mL are maintained. After cessation of male hormonal contraception, sperm output fully recovers in a predictable manner, resulting in pregnancies and livebirths. Spontaneous miscarriage and fetal malformation rates after recovery of sperm output overlap those in the general population. Short-term adverse events—acne, night sweats, increased weight, and altered mood and libido—are recognised, but are generally mild. Further optimisation of specific androgen-progestin regimens and phase 3 studies of lead combinations are still needed to successfully develop an approved male hormonal contraceptive and to identify long-term side-effects.